YIG ferrite material with high dielectric constant and high saturation magnetization and preparation method thereof

By doping Zr4+, Sn4+, Zn2+, Bi3+, Ca2+ in YIG ferrite materials, the dielectric constant and saturation magnetization of the material are regulated, and the problem of insufficient saturation magnetization of existing materials is solved, and high dielectric constant and The material preparation with high saturation magnetization meets the needs of miniaturization and lightweighting of 5G base station circulators.

CN119143496AActive Publication Date: 2024-12-17TAIYUAN UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202411280020.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-17
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

The saturation magnetization of existing high-dielectric constant YIG ferrite materials is small, resulting in increased device loss and limited engineering application range. Doping with high polarization ions will lead to wide ferromagnetic resonance lines, affecting the device miniaturization needs. .

Method used

By doping Zr4+, Sn4+, Zn2+ plasma combination, partially replacing Fe3+, combined with the use of Bi3+ and Ca2+, the saturation magnetization and dielectric constant of the material are regulated, and specific chemical composition and preparation methods are used to improve the dielectric constant and saturation of the material. Magnetization intensity.

Benefits of technology

The dielectric constant is increased to 30~35 and the saturation magnetization strength reaches 1800~2000Gs, meeting the needs of miniaturized and lightweight 5G base station circulators, reducing device size and improving stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143496A_ABST
    Figure CN119143496A_ABST
Patent Text Reader

Abstract

The invention provides a YIG ferrite material with high dielectric constant and high saturation magnetization and a preparation method thereof, and belongs to the field of microwave ferrite materials, the chemical formula of the YIG ferrite material is BiaCabY3-a-bZrbSncZncFe5-b-2c-delta O12, 1.2 < = a < = 1.5, 0 < = b < = 0.6, 0 < = c < = 0.5, delta is iron deficiency, 0 < = delta < = 0.3, the dielectric constant of the YIG ferrite material is 30-35, and the saturation magnetization is 1800-2000 Gs. The YIG ferrite material provided by the invention is simple in preparation method, can be used in miniaturized microwave devices, and can meet the requirements of miniaturization and light weight of 5G base station circulators.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of YIG ferrite, in particular to a YIG ferrite material with high dielectric constant and high saturation magnetization intensity and a preparation method thereof. Background Art

[0002] The purpose of developing high dielectric constant YIG ferrite materials is to solve the problem of miniaturization of ferrite microwave devices. The dielectric constant of traditional YIG ferrite materials is 13-15. When designing low-frequency circulator isolators, the device size is too large and cannot meet the needs of miniaturization and integration. According to the ferrite device theory, if the 5G base station circulator prepared by YIG ferrite wants to further miniaturize and lighten the device, improving the dielectric constant of YIG ferrite has become an important means.

[0003] In the last century, there were articles reporting that doping high-polarized ions into YIG ferrite can effectively increase the dielectric constant of YIG ferrite. In recent years, there have been some patent documents on high dielectric constant YIG ferrite materials and manufacturing methods, such as patent publication number CN112960977A, titled "A high dielectric constant microwave ferrite material, preparation method and application thereof", publication number CN116854460A, titled "A high dielectric constant, high Curie temperature and low loss microwave ferrite material and preparation method thereof", publication number CN111825441A, titled "High dielectric constant, high saturation magnetization intensity garnet ferrite material, preparation method and application thereof", etc. Although these ferrite materials can improve the dielectric constant to a certain extent compared with traditional materials, for example, the dielectric constant of CN112960977A can be increased to more than 18, the dielectric constant of CN116854460A can be increased to 16-23, and the dielectric constant of CN111825441A can be increased to 32-33.

[0004] However, these existing YIG ferrite materials all have some problems: for example, compared with traditional YIG ferrite materials, the saturation magnetization intensity of high dielectric constant YIG ferrite materials is smaller, and the YIG ferrite material in the circulator requires sufficient saturation magnetization intensity to ensure the use frequency and efficiency of the circulator. In order to improve the dielectric constant of the material, doping with highly polarized ions will cause the ferromagnetic resonance line width of the YIG ferrite material to be larger and the Curie temperature to be lower, which will increase the device loss and affect the scope of engineering application. For this reason, the present invention proposes a high dielectric constant, high saturation magnetization intensity YIG ferrite material and a preparation method thereof to solve the above-mentioned problems. Summary of the invention

[0005] The object of the present invention is to provide a high dielectric constant, high saturation magnetization YIG ferrite material and a preparation method thereof, which is suitable for miniaturized, highly integrated, and highly stable 5G base station circulators.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a high dielectric constant and high saturation magnetization YIG ferrite material, the chemical formula of which is: Bi a Ca b Y 3-a-b Zr b Sn c Zn c Fe 5-b-2c-δ O 12 , where 1.2≤a≤1.5, 0≤b≤0.6, 0≤c≤0.5, δ is the amount of iron deficiency, 0≤δ≤0.3.

[0008] The present invention adopts Zr doping 4+ Sn 4+ 、Zn 2+ Plasma combined, partial replacement of Fe 3+ Controlling the saturation magnetization of materials, especially Zn 2+ It is a large radius ion with a large number of d orbital electrons, which plays a role in increasing the ion polarizability and thus increasing the dielectric constant of the material; using Bi 3+ , Ca 2+ Partial replacement of Y 3+ , adjust the saturation magnetization, especially the Bi 3+ , which is a highly polarized ion and plays a role in increasing the dielectric constant.

[0009] The present invention also provides a method for preparing the above-mentioned high dielectric constant and high saturation magnetization YIG ferrite material, comprising the following steps:

[0010] S1. Weigh the corresponding Fe according to the chemical formula 2 O 3 , Y 2 O 3 、Bi 2 O 3 、CaCO 3 、ZrO 2 SnO 2 and ZnO powder, and then ball milled for the first time, and the obtained slurry is dried;

[0011] S2, sieving the powder dried in S1 and pre-sintering it;

[0012] S3, ball milling the pre-burned powder in S2 for a second time, followed by drying;

[0013] S4, granulating and sieving the powder after the secondary ball milling and drying in S3, and then pressing and molding to obtain a ferrite green body;

[0014] S5. Sintering the ferrite green body to obtain the YIG ferrite with high dielectric constant and high saturation magnetization.

[0015] As a preferred technical solution of the present invention, in S1, the Fe 2 O 3 , Y 2 O 3 、Bi 2 O 3 、CaCO 3 、ZrO 2 SnO 2 The purity of ZnO powder is ≥99%.

[0016] As the preferred technical solution of the present invention, the first ball milling in S1 and the secondary ball milling in S4 both use a plasma ball mill, the ball milling jar is connected to an electrode, the grinding media are all stainless steel balls, the mass ratio of large, medium and small balls is 1:(2-3):(1-2), the dispersant is all deionized water, and the mass ratio of material, balls and water is 1:(4-6):(4-6); the specific process of the first ball milling in S1 and the secondary ball milling in S4 is the same, both are: run for 30 minutes and stop for 10 minutes, cycle 12 times, the rotation speed is 800-950rad / min, and the effective ball milling time is 6-9h.

[0017] As a preferred technical solution of the present invention, the pre-sintering temperature is 700-750° C. and the time is 3-4 hours.

[0018] As a preferred technical solution of the present invention, in S1 and S3, the drying temperature is 80-100°C.

[0019] As a preferred technical solution of the present invention, in S4, the adhesive used for granulation is a 5-7wt% PVA aqueous solution, 5-7g of ferrite powder is weighed for sample preparation, and the amount of adhesive is 10-15% of the weight of the weighed ferrite powder.

[0020] As a preferred technical solution of the present invention, the pressure during the compression molding is 15 to 20 MPa, and the pressure holding time is 4 to 6 minutes.

[0021] As the preferred technical solution of the present invention, the sintering process is specifically as follows: from room temperature to 150°C for 1h, keeping warm for 1h for drainage, from room temperature to 550°C for 2h, keeping warm for 1h for debinding, from room temperature to 900°C for 2h, keeping warm for 4h, from room temperature to 500°C for 2h and then cooling with the furnace.

[0022] The present invention also provides an application of the above-mentioned high dielectric constant and high saturation magnetization intensity YIG ferrite material in microwave devices.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The dielectric constant of the ferrite material provided by the present invention is 30 to 35, and at the same time has a relatively high saturation magnetization intensity, which reaches 1800 to 2000Gs. These advantages can effectively reduce the size of the device, so that it can be used in miniaturized microwave devices, meeting the miniaturization and lightweight requirements of 5G base station circulators. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 X-ray diffraction patterns of the YIG ferrites prepared in Example 2 and Example 6;

[0027] Figure 2 The hysteresis loop diagram of the YIG ferrite prepared in Example 2 and Example 6;

[0028] Figure 3 The dielectric constant spectra of the YIG ferrites prepared in Example 2 and Example 6 are shown. DETAILED DESCRIPTION

[0029] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0030] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0031] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0034] The raw materials used in the following examples are all commercially available conventional raw materials, without special limitation; the Fe 2 O 3 , Y 2 O 3 、Bi 2 O 3 、CaCO 3 、ZrO 2 SnO 2 The purity of ZnO powder is ≥99%. The following description will not be repeated.

[0035] Example 1

[0036] S1, according to the chemical formula Bi 1.4 Ca 0.3 Y 1.3 Zr 0.3 Sn 0.1 Zn 0.1 Fe 4.4 O 12 Weigh Fe in proportion 2 O 3 , Y 2 O 3 、Bi 2 O 3 、CaCO 3 、ZrO 2 SnO 2, ZnO powder was placed in a ball mill, loaded into a plasma ball mill, and ball milled with stainless steel balls as grinding media and deionized water as dispersant. The mass ratio of large, medium and small balls in the plasma ball mill was 1:2.5:1.5, and the mass ratio of material, ball and water was 1:5:4. The ball milling mode was cyclic discharge, the discharge frequency was 30.5KHz, the discharge power was 15W, and it was stopped for 10 minutes every 30 minutes of operation, 12 cycles, the rotation speed was 895rad / min, and the effective ball milling time was 8h. The drying oven temperature was 80℃.

[0037] S2. The dried powder is sieved through a 30-mesh sieve and placed in a muffle furnace for pre-sintering, and calcined at 750°C for 3 hours.

[0038] S3, the pre-burned powder is placed in a plasma ball mill for secondary ball milling, with the parameters unchanged, the same as S1; after the ball milling, it is placed in a drying oven at 80°C for drying.

[0039] S4. The ferrite powder after the second grinding is placed in a mortar for granulation. While grinding manually, 5 wt% PVA aqueous solution is added as a binder, and the amount of the binder is 12% of the mass of the powder; then, 6.5 g of the granulated and sieved powder is weighed through a 40-mesh sieve, and a pressure of 18 MPa is applied using a hydraulic sample making machine, and the pressure is maintained for 5 minutes, and then demolding is performed to obtain a ferrite green embryo.

[0040] S5. Place the ferrite green body in a muffle furnace, and the sintering process is: 1 hour from room temperature to 150°C, keep warm for 1 hour to drain, 2 hours to 550°C, keep warm for 1 hour to debind, 2 hours to 900°C, keep warm for 4 hours, 2 hours to 500°C and then cool with the furnace.

[0041] Example 2

[0042] S1, according to the chemical formula Bi 1.4 Ca 0.3 Y 1.3 Zr 0.3 Sn 0.2 Zn 0.2 Fe 4.2 O 12 Weigh Fe in proportion 2 O 3 , Y 2 O 3 、Bi 2 O 3 、CaCO 3 、ZrO 2 SnO 2, ZnO powder was placed in a ball mill, loaded into a plasma ball mill, and ball milled with stainless steel balls as grinding media and deionized water as dispersant. The mass ratio of large, medium and small balls in the plasma ball mill was 1:2.5:1.5, and the mass ratio of material, ball and water was 1:5:4. The ball milling mode was cyclic discharge, the discharge frequency was 30.5KHz, the discharge power was 15W, and it was stopped for 10 minutes every 30 minutes of operation, 12 cycles, the rotation speed was 895rad / min, and the effective ball milling time was 8h. The drying oven temperature was 100℃.

[0043] S2. The dried powder is sieved through a 30-mesh sieve and placed in a muffle furnace for pre-sintering, and calcined at 700°C for 4 hours.

[0044] S3, the pre-burned powder is placed in a plasma ball mill for secondary ball milling, with the parameters unchanged, the same as S1; after the ball milling, it is placed in a drying oven at 100°C for drying.

[0045] S4. The ferrite powder after the second grinding is placed in a mortar for granulation. While grinding manually, 6 wt% PVA aqueous solution is added as a binder, and the amount of the binder is 12% of the powder mass; then, 6.5 g of the granulated and sieved powder is weighed through a 40-mesh sieve, and a pressure of 20 MPa is applied using a hydraulic sample making machine, and the pressure is maintained for 4 minutes, and then demolding is performed to obtain a ferrite embryo.

[0046] S5. Place the ferrite green body in a muffle furnace, and the sintering process is: 1 hour from room temperature to 150°C, keep warm for 1 hour to drain, 2 hours to 550°C, keep warm for 1 hour to debind, 2 hours to 900°C, keep warm for 4 hours, 2 hours to 500°C and then cool with the furnace.

[0047] Example 3

[0048] S1, according to the chemical formula Bi 1.4 Ca 0.3 Y 1.3 Zr 0.3 Sn 0.2 Zn 0.2 Fe 4.2 O 12 Weigh Fe in proportion 2 O 3 , Y 2 O 3 、Bi 2 O 3 、CaCO 3 、ZrO 2 SnO 2, ZnO powder was placed in a ball mill, loaded into a plasma ball mill, and ball milled with stainless steel balls as grinding media and deionized water as dispersant. The mass ratio of large, medium and small balls in the plasma ball mill was 1:2.5:1.5, and the mass ratio of material, ball and water was 1:5:4. The ball milling mode was cyclic discharge, the discharge frequency was 30.5KHz, the discharge power was 15W, and it was stopped for 10 minutes every 30 minutes of operation, 12 cycles, the rotation speed was 895rad / min, and the effective ball milling time was 8h. The drying oven temperature was 110℃.

[0049] S2. The dried powder is sieved through a 30-mesh sieve and placed in a muffle furnace for pre-sintering, and calcined at 750°C for 4 hours.

[0050] S3, the pre-burned powder is placed in a plasma ball mill for secondary ball milling, with the parameters unchanged, the same as S1; after the ball milling, it is placed in a drying oven at 110°C for drying.

[0051] S4. The ferrite powder after the second grinding is placed in a mortar for granulation. While grinding manually, 7 wt% PVA aqueous solution is added as a binder, and the amount of the binder is 12% of the powder mass; then, 6.5 g of the granulated and sieved powder is weighed through a 40-mesh sieve, and a pressure of 20 MPa is applied using a hydraulic sample making machine, and the pressure is maintained for 5 minutes, and then demolding is performed to obtain a ferrite green embryo.

[0052] S5. Place the ferrite green body in a muffle furnace, and the sintering process is: 1 hour from room temperature to 150°C, keep warm for 1 hour to drain, 2 hours to 550°C, keep warm for 1 hour to debind, 2 hours to 950°C, keep warm for 4 hours, 2 hours to 500°C and then cool with the furnace.

[0053] Example 4

[0054] YIG Ferrite Material Bi 1.2 Y 1.8 Sn 0.5 Zn 0.5 Fe 3.7 O 12 The preparation steps are the same as those in Example 1.

[0055] Example 5

[0056] YIG Ferrite Material Bi 1.5 Ca 0.6 Y 0.9 Zr 0.6 Sn 0.1 Zn 0.1 Fe 4.2 O 12 The preparation steps are the same as those in Example 2.

[0057] Example 6

[0058] YIG Ferrite Material Bi1.4 Ca 0.3 Y 1.3 Zr 0.3 Fe 4.6 O 12 The preparation steps are the same as those in Example 2.

[0059] Figures 1 to 3 The X-ray diffraction diagram, hysteresis loop diagram and dielectric constant spectrum of the YIG ferrite prepared in Example 2 and Example 6 are shown respectively. Figure 1 It can be seen that both Example 2 and Example 6 obtain a single-phase garnet ferrite. Figure 2 It can be seen that the saturation magnetization of the ferrite obtained in Example 2 and Example 6 is 1908Gs and 1827Gs respectively. Figure 3 It can be seen that the dielectric constants of the ferrites obtained in Example 2 and Example 6 are 34.2 and 30.5 respectively.

[0060] Comparative Example 1

[0061] YIG Ferrite Material Bi 1.4 Ca 0.5 Y 1.1 Zr 0.3 Sn 0.2 Fe 4.4 O 12 The preparation steps are the same as those in Example 2.

[0062] Comparative Example 2

[0063] YIG Ferrite Material Y 3 Sn 0.2 Zn 0.2 Fe 4.2 O 12 The preparation steps are the same as those in Example 2.

[0064] Comparative Example 3

[0065] YIG Ferrite Material Y 2.7 Ca 0.3 Zr 0.3 Sn 0.2 Zn 0.2 Fe 4.2 O 12 The preparation steps are the same as those in Example 2.

[0066] Comparative Example 4

[0067] YIG Ferrite Material Bi 1.4 Ca 0.3 Y 1.3 Zr 0.3 Sn 0.2 Zn 0.2 Fe 4.1O 12 The preparation steps are the same as those in Example 3.

[0068] Comparative Example 5

[0069] YIG Ferrite Material Bi 1.4 Ca 0.5 Y 1.1 Zr 0.3 Sn 0.2 Fe 4.4 O 12 The preparation steps are the same as those in Example 3.

[0070] Table 1 shows the ferrite performance test results of Examples 1-6 and Comparative Examples 1-5.

[0071] Table 1 Ferrite performance data table of Examples 1 to 6 and Comparative Examples 1 to 5

[0072]

[0073] As shown in Table 1, the dielectric constant and saturation magnetization of the YIG ferrite obtained by Sn-Zn co-doping in Example 2 are better than those of the YIG ferrite in Comparative Example 1; 3+ The dielectric constant of the YIG ferrite obtained by doping is significantly improved compared with that of Comparative Examples 2 and 3, indicating that the appropriate amount of Bi 3+ Doping can significantly improve the dielectric constant of YIG ferrite; the iron deficiency in Example 3 and Comparative Example 4 is 0.1 and 0.2 respectively, and the YIG ferrite obtained with an iron deficiency of 0.1 has better performance; it can be seen from Example 3 and Comparative Example 5 that Sn-Zn co-doping is better than Sn 2+ The doped YIG ferrite has better performance.

[0074] In summary, the present invention adjusts the composition of the YIG ferrite material by Ca 2+ 、Zr 4+ Sn 4+ 、Zn 2+ And Bi 3+ The synergistic addition of Bi and Zn improves the dielectric constant, so that the saturation magnetization of the obtained material is between 1800 and 2000 Gs, and the dielectric constant is 30 to 35; moreover, the sintering temperature of YIG ferrite without adding Bi and Zn is currently 1400 to 1450°C. 2 O 3 The melting point of ZnO is lower than that of ZnO. The raw materials with lower melting points may form a molten phase at a lower temperature, thereby reducing the overall sintering temperature. The chemical composition of the high dielectric constant YIG ferrite material provided by the present invention is 3+ With Zn 2+The synergistic addition reduces the sintering temperature of the material, avoids excessive grain growth caused by too high sintering temperature and too long sintering time, and is conducive to the formation of ferrite materials with good grain size distribution.

[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A high dielectric constant and high saturation magnetization YIG ferrite material, characterized in that: The chemical formula is:Bi a Ca b Y 3-a-b Zr b Sn c Zn c Fe 5-b-2c-δ O 12 , where 1.2≤a≤1.5, 0≤b≤0.6, 0≤c≤0.5, δ is the amount of iron deficiency, 0≤δ≤0.

3.

2. A method for preparing the high dielectric constant and high saturation magnetization YIG ferrite material according to claim 1, characterized in that: The following steps are involved: S1. Weigh the corresponding Fe2O3, Y2O3, Bi2O3, CaCO3, ZrO2, SnO2 and ZnO powders according to the chemical formula, mix them and perform the first ball milling, and dry the obtained slurry; S2, sieving the powder dried in S1 and pre-sintering it; S3, ball milling the pre-burned powder in S2 for a second time, followed by drying; S4, granulating and sieving the powder after the secondary ball milling and drying in S3, and then pressing and molding to obtain a ferrite green body; S5. Sintering the ferrite green body to obtain the YIG ferrite with high dielectric constant and high saturation magnetization.

3. The preparation method according to claim 2, characterized in that: In S1, the purity of the Fe2O3, Y2O3, Bi2O3, CaCO3, ZrO2, SnO2 and ZnO powders is ≥99%.

4. The preparation method according to claim 2, characterized in that: The first ball milling in S1 and the second ball milling in S4 both use plasma ball mills, the ball milling jar is connected to electrodes, the grinding media are all stainless steel balls, the mass ratio of large, medium and small balls is 1: (2-3): (1-2), the dispersant is all deionized water, and the mass ratio of material, balls and water is 1: (4-6): (4-6); the specific processes of the first ball milling in S1 and the second ball milling in S4 are the same, both are: run for 30 minutes and stop for 10 minutes, cycle 12 times, the rotation speed is 800-950 rad / min, and the effective ball milling time is 6-9 hours.

5. The preparation method according to claim 2, characterized in that: The pre-sintering temperature is 700-750° C. and the time is 3-4 hours.

6. The preparation method according to claim 2, characterized in that: In S1 and S3, the drying temperature is 80-100°C.

7. The preparation method according to claim 2, characterized in that: In S4, the adhesive used in the granulation is a 5-7 wt% PVA aqueous solution, and the amount of the adhesive used is 10-15% of the weight of the ferrite powder.

8. The preparation method according to claim 2, characterized in that: The pressure during the compression molding is 15-20 MPa, and the pressure holding time is 4-6 minutes.

9. The preparation method according to claim 2, characterized in that: The sintering temperature is 900-950° C., and the sintering time is 3-5 hours.

10. Use of the high dielectric constant and high saturation magnetization YIG ferrite material according to claim 1 in microwave devices.

Citation Information

Patent Citations

  • Garnet ferrite material with high dielectric constant and high saturation magnetization intensity and preparation method and application thereof

    CN111825441A

  • Garnet ferrite material with high dielectric constant and preparation method thereof

    CN112456998A

  • Microwave ferrite material with high dielectric constant as well as preparation method and application of microwave ferrite material

    CN112960977A

  • Low-temperature sintered YIG gyromagnetic ferrite material and preparation method thereof

    CN113233885A

  • High-performance high-dielectric-constant gyromagnetic ferrite material and preparation method thereof

    CN116813321A

Cited By

  • Low-temperature sintered high-dielectric-constant ferrite material and preparation method thereof

    CN120309333A

  • Composite ferrite, preparation method thereof, circulator and application

    CN120709018A